Exploring Loneliness and Homesickness among Students at Dayah in Aceh Besar - Muhammad Alka; Iyulen Pebry Zuanny; Safrilsyah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2026)
Students (santri) attending Dayah and separated from their families frequently experience negative emotions, including difficulty adapting to a new environment and a longing for the atmosphere of home, a condition referred to as homesickness. One of the factors that influences homesickness is loneliness. This study aims to examine the relationship between loneliness and homesickness among santri at dayah. This study employed a quantitative approach using a correlational method. The instruments used in this study were the loneliness scale and the homesickness scale. The sampling technique employed total sampling, encompassing all 90 santri at the dayah, aged 13 to 19 years, enrolled in grades 7 through 12. This study employed quantitative analysis using Pearson’s product moment correlation test. The results indicated a highly significant positive relationship between loneliness and homesickness among santri at the dayah, with a correlation coefficient (r) of 0.644 and a significance value of 0.000 (p < 0.05). This implies that higher levels of loneliness are associated with higher levels of homesickness, and vice versa.